The New Fiqh in A National School of Legal Thought: A Paradigm Shift in National School of Islamic Law on M. Barry Hooker’s Perspective - Wildani Hefni (Justicia Islamica, 2020)
The polemic of the domain between religious regulation and state authority in the national school of Islamic law in Indonesia seems to be endlessly debated by Indonesian and Western Scholars, Muslims, and non-muslims. This article discusses western scholarly discourses on the National School of Islamic law by examining the thoughts and works of M. Barry Hooker. Hooker introduced the term “new fiqh” in the national school of Islamic discourse and explained that the state's Indonesian fiqh was instrumentalized. Based on the model of the study of public figures and grounded its primary data of Hooker’s work, this paper shows that Hooker criticizes the shifting paradigm of classical fiqh text to fiqh dominated by the state. The state determines the process of fiqh with various instruments and public transmission of sharia, including religious bureaucratization, state intervention in the Islamic legal education curriculum, and religious pulpit mediums.